Effect of Parents Education on Childs Oral Health - Aurangjeb, AM; Zaman, T (Bangladesh Journal of Dental Research & Education, 2013)
Children under the age of 12 years generally spend most of their time with their parents and guardians even when they attend schools. It has been found that young children's oral health maintenance and outcomes are influenced by their parent's knowledge and beliefs, and knowledge and beliefs are influenced by their educational background. This study was done to assess the relation between parents education and their childs oral health. Parents of children aged 3-12 years, attending The Dhaka Project School, Dokkhin Khan, Uttara, Dhaka were invited to participate in the study. A 17-item questionnaire covering socio-demographic characteristics, dietary practices and oral hygiene practices was distributed to their parents and a 8 item checklist was used during their visit to the school. Responses of the parents and findings of oral health of children were recorded. The sample comprised of 251 parents either mother or father, with the mean age of children being 5.65 years. Mean plaque index 1.60, calculus index 1.30, gingivitis index 1.11, decayed teeth index 1.69, missing teeth index 0.22 and filled teeth index was 0.07. Parents with higher educational qualification and information gained through dentist had a better knowledge about child's oral health. DOI: http://dx.doi.org/10.3329/bjdre.v3i2.16609 Bangladesh Journal of Dental Research & Education Vol.3(2) 2013: 26-28